The Effectiveness of Using E-Learning as a Learning Media during the Covid-19 Pandemic - Elda Permata Sari; Muldi Yuhendri (EDUTEC : Journal of Education And Technology, 2021)
This study aims to determine the effectiveness of using E-learning as a learning medium during the COVID-19 pandemic in the January-June 2021 semester of the Technology and Vocational Education study program, Padang State University. This research is descriptive research with quantitative method. Data collection techniques using a questionnaire given via google form, where the data analysis technique is to see the achievement of the existing indicators. The subjects of this study were postgraduate students of technology and vocational education in the 2020 entry year of the Faculty of Engineering, Padang State University. Based on data analysis, it was found that quantitative data, indicators of learning objectives were seen that the respondent's achievement level (TCR) reached 77.20% with sufficient category. The indicator of learning infrastructure shows that the TCR reaches 82.07% with a good category. The indicator of the ability to use technology is seen that the TCR reaches 81.18% in the good category. The time efficiency indicator shows that the TCR reaches 81.93% with a good category. Indicators of learning outcomes seen that the TCR reached 86.70%. Thus, it can be concluded that the use of E-learning as a learning medium during the COVID-19 pandemic is categorized as effective, it can be seen from the results of research on 5 indicators, there are 4 indicators which are in good category and 1 is in sufficient category.